ANALISIS KARAKTERISTIK PEKERJAAN, KEPUASAN KERJA DAN KINERJA KARYAWAN (STUDI KASUS PADA CV SAPUTRA JAYA CIMAHI) - Edisa, Nefertari; Senen, Syamsul Hadi; Masharyono, Masharyono (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this research is to know the decription of job characteristics, job satisfaction and job performance.Design/methodology/approach - The Research design is cross sectional. This research is using descriptive approach with explanatory survey method. The analysis unit is 75 employees. Collecting the data is using questionnaire. Analysis technique used is descriptive technique with using frequency distribution.Finding - Based on the result of research, the results obtained that job characteristics in the category is appropriate with the score 86%, job satisfaction is in the high category with a score 85% and job performance is in high category with a score 87%.Originality/value - This research giving a basic for understanding job characteristics, job satisfaction and job performance issues on employee. The difference of this research with the previous research are on the object, variable, theory and references.Â